Pelatihan Pembuatan Produk Hiasan Buah Merah Dari Kawat Buluh Pada Remaja Kompleks Malanu, Kota Sorong - Angelika Tauran; Johanis Gemenop; Lisa Novelsia Wattimena; Rasdy Panggara; Fensca F. Lahallo (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
Training on making decorative products from Papuan red fruit using feather wire for teenagers in the Malanu complex, Sorong City, aims to develop craft arts skills and appreciate the richness of local culture. This training was carried out with the aim of increasing creativity and empowering teenagers to produce decorative products that are aesthetic and have high artistic value. Training methods include observation, preparation and implementation. As a result, the teenagers from the Malanu complex succeeded in producing decorative products that reflected local Papuan identity and demonstrated impressive artistic abilities. These results were also strengthened by the results of the questionnaire which showed that there were 3 questions to assess participants' understanding and abilities regarding the material and practice, including: Fruit shape. red, materials and tools, as well as product manufacturing steps. Of the 11 participants, 8 people had an understanding of the material and training and 3 other people had sufficient understanding. Thus, it can be concluded that the training activities can be understood by participants.